Inheritance Law five years after Civil and Commercial Code - Ferrer, Francisco A. M. (Universidad Nacional del Litoral, 2020)
Five years after the adoption of the new Civil and Commercial Code, and regarding the law of wills, we balance its good points, innovations and improvements in certain aspects from the previous Code, as well as the deficiencies to be c orrected by the legislator. We conclude the balance is positive and that this new regulation represents a new stage in the legal evolution, and an improvement in the regulation of the law of wills in Argentina.